Cross-sections for production of In115m by quasi-monoenergetic neutrons within 7-20 MeV. (October 2022) - Hingu, Akash; Soni, Bhargav; Parashari, Siddharth; Makwana, Rajnikant; Prajapati, P.M.; Vashi, Vibhuti; Mehta, Mayur; Palit, R.; Suryanarayana, S.V.; Nayak, B.K.; Katovsky, K.; Mukherjee, S.
Abstract: The measurement of cross-sections producing I n 115 m has been carried out within the energy range of 7–20 MeV. The neutron activation analysis (NAA) followed by off-line γ -ray spectrometry have been used for the purpose. The quasi-monoenergetic neutron beam was produced using the L i ( p, n ) 7 reaction at the 14UD BARC-TIFR Pelletron accelerator facility at Mumbai, India. The ratio technique of covariance analysis has been used to estimate the uncertainty and correlation between the current experimental data which considers the collective uncertainty from all the attributes in the measurement. The measured cross-sections were compared with the experimental data from the previous literatures, different evaluated data libraries such as ENDF/B-VIII.0, JEFF-3.3, JENDL-4.0, CENDL-3.2 and the theoretically predicted results using the TALYS 1.95 and EMPIRE 3.2.3. The experimental results presented in this work are crucial for the measurement of neutron flux in the NAA technique. Highlights: Cross-section of I n ( n, n ′ ) 115 m 115 I n reaction has been measured using the standard neutron activation analysis technique. The measured cross-sections are compared with results of previous literatures and with the evaluated data libraries. Theoretical calculations have been performed using nuclear modular code TALYS-1.95 and EMPIRE-3.2.3. A detailed covariance analysis has been used to measure uncertainties in the measured data.